Analisis Faktor Yang Memengaruhi Wajib Pajak Untuk Melakukan Tax Evasion - Widyasari; Syanti Dewi; Nataherwin (Universitas PGRI Yogyakarta, 2022)
This study aims to evaluate the effect of tax justice, money ethics, understanding of taxation, tax rates and tax sanctions on tax evasion. Tax evasion in Indonesia is an important problem that is being faced by the tax apparatus. Even though there are laws and regulations, there are still taxpayers who commit tax evasion. This research can help the government, so that they know the factors that can significantly influence tax evasion. This research method is measured using the SmartPLS version 3 data processing program which refers to the value generated by Cronbach's alpha and composite reliability, with 75 respondents as research subjects from UMKM taxpayers . The results of this study indicate that the variables of tax justice, money ethics, tax rates have a significant positive effect on tax evasion. While the understanding of taxation does not have a significant negative effect, and tax sanctions have a significant negative effect. The implication of this research is that the hypothesis of tax justice and understanding of taxation is rejected, and the hypothesis of money ethics, tax rates, and tax sanctions are accepted.